TRACE ELEMENT ANALYSIS OF SOME MEDICINAL HERBS BY PROTON INDUCED X-RAY EMISSION (PIXE) - Ahmad, N.; Naseem, A.; Saadat, S.; Shahnawaz, M.; Rafique, M. (The Nucleus, 2013)
Proton induced X-ray Emission (PIXE) has been used to investigate the concentration of nineteen trace elements in eleven medicinal herbs commonly used for the treatment of different diseases in Pakistan. Mg, Si, K, Ca and Fe were detected in all the medicinal herbs studied. Germanium has been detected only in violet flower. Indian Lilac, field marigold and violet flower have the highest number of trace elements with maximum concentration. No toxic elements such as Pb, Hg etc. were detected in these medicinal herbs. The accuracy of our results was validated by analyzing standard reference material Citrus Leaf (NIST- SRM -1572). Results indicate that medicinal herbs are a rich source of trace elements which may be useful for the cure of certain ailments.